Serum S100A12 Levels Are Correlated With the Presence and Severity of Coronary Artery Disease in Patients With Type 2 Diabetes Mellitus. (1st June 2013) - Zhao, Peng; Wu, Mingchun; Yu, Houyou; Huang, Yang; Wang, Yutong; Wang, Wei; Yin, Wen
Abstract : Objective: Patients with type 2 diabetes mellitus (T2DM) are at high risk for development of atherosclerosis and cardiovascular events. Serum S100A12 levels have been reported to be associated with coronary artery disease (CAD) and T2DM. We sought to assess whether serum S100A12 levels are correlated with the presence and severity of CAD. Methods: Type 2 diabetes mellitus levels in 188 consecutive patients with T2DM undergoing coronary angiography for the evaluation of CAD. The severity of CAD was assessed by the Coronary Atherosclerosis Index (CAI) scores. Results: Serum S100A12 levels were significantly higher in patients with T2DM with CAD than in those without CAD. Multivariate logistic regression analysis revealed that serum S100A12 levels were independently associated with the presence of CAD. Serum S100A12 levels were positively correlated with the Coronary Atherosclerosis Index scores after adjusting for other clinical characteristics. Conclusion: High S100A12 levels are associated with the presence and severity of CAD in patients with T2DM.